The dusty and extremely red progenitor of the type II supernova 2023ixf in Messier 101 - Xiang, Danfeng; Mo, Jun; Wang, Lingzhi; Wang, Xiaofeng; Zhang, Jujia; Lin, Han; Wang, Lifan (Science China. Physics, mechanics & astronomy, 2024)
Stars with initial masses in the range of 8–25 solar masses are thought to end their lives as hydrogen-rich supernovae (SNe II). Based on the pre-explosion images of Hubble space telescope (HST) and Spitzer space telescope, we place tight constraints on the progenitor candidate of type IIP SN 2023ixf in Messier 101. Fitting of the spectral energy distribution (SED) of its progenitor with dusty stellar spectral models results in an estimation of the effective temperature as 3091 −258 +422 K. The luminosity is estimated as lg( L / L ⊙ )∼4.83, consistent with a red supergiant (RSG) star with an initial mass of 12 −1 +2 M ⊙ . The derived mass loss rate (6×10 −6 −9×10 −6 M ⊙ yr −1 ) is much lower than that inferred from the flash spectroscopy of the SN, suggesting that the progenitor experienced a sudden increase in mass loss when approaching the final explosion. In the infrared bands, significant deviation from the range of regular RSGs in the color-magnitude diagram and period-luminosity space of the progenitor star indicates enhanced mass loss and dust formation. Combined with new evidence of polarization at the early phases of SN 2023ixf, such a violent mass loss is likely a result of binary interaction.